Analysis of mandibular position using different methods of location. - Venturelli, Farley Augusto; Zuim, Paulo Renato Junqueira [UNESP]; Antenucci, Rosse Mary Falcón; Garcia, Alício Rosalino (My University, 2009)
There has been much discussion regarding the ideal position of the condyle in the mandibular fossa. Although the centric relation position (CR) is used as a reference, some authors do not believe that it is physiologic. Thus, the aim of this study was to evaluate in a group of asymptomatic individuals the position of the condyle in the mandibular fossa at maximum intercuspation (MI), with a occlusal splint and with a Lucia jig between the teeth. It was analyzed by means of magnetic resonance imaging (MRI), transcranial radiography imaging and analysis of horizontal axis of rotation from casts mounted on an articulator. The results showed that even if patients had mandibular displacement in positions of CR, habitual maximum intercuspation and with the occlusal splint, confirmed by means of the analysis of the horizontal axis of rotation, the images showed no statistically significant differences among condylar positions. It can therefore be concluded that the positions analyzed were similar and that transcranial radiography seems to be a reliable method for analyzing condylar position.
Keywords: adult; dentistry; female; histology; human; mandible; methodology; Adult; Dentistry; Female; Humans; Mandible; Young Adult